Importance of Quality Concepts in Education Industry in the Current Trend – Review - P.Sivasankaran; S.Senthil Kumaran; P.Natarajan (International Journal of Engineering and Management Research, 2022)
Quality is the main important key aspects in the global scenario in the recent past. Without quality nothing cannot be improved in the processes done by the individuals in every day today activities. In this work quality concept in education applications is focused in extensive way. Higher learning engineering institutes taken as important focus to study the various metrics in terms of evaluating the quality function in education performance system and other allied areas like research, funding etc. To implement Quality culture in any organization all members must coordinate themselves in professional conduct without violating the quality principles in education system. The most important factor in bringing the quality system in education industry is to empower all minds of people by properly guiding them as team. Next important factor is respect for others as per TQM principles every persons working in organization must respect other ideas and feelings without showing any discrimination with respect to caste, religion and other Alma matters. Employee empowerment, team work and respect for others are the main key element which helps to improve the quality system of organization. In this paper pros and cons of present education system in engineering institutes are discussed with valid background through survey mechanism.